Oxidation of nitric oxide by atmospheric pressure plasma in a resonant plasma reactor - Yumii, Takayoshi; Yoshida, Takashi; Doi, Kyoji; Kimura, Noriaki; Hamaguchi, Satoshi (Journal of physics. D, Applied physics, 2013)
A novel non-equilibrium atmospheric-pressure-plasma generation system is proposed. The system discussed in this study is specifically designed for nitrogen oxide (NOx) gas treatment. A plasma is generated by a high-voltage radio-frequency (RF) electric field formed in the system that accumulates electromagnetic energy by resonance provided by a low-voltage power supply. With an input RF voltage of 100-200 V, a high voltage of 4k-8 kV at the same frequency can be formed on the powered electrode of the system under the resonance conditions. The plasma generator also serves as a plasma reactor, in which nitric oxide (NO) can be efficiently oxidized to form nitrogen dioxide (NO2) in the presence of oxygen (O2) at atmospheric pressure. It has been shown that, in terms of NO oxidation efficiency, the resonant plasma reactor proposed in this study is comparable or even superior to some of the previously proposed NO oxidation systems.